2009
DOI: 10.1021/ma900483n
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Polystyrene-block-poly(2-vinylpyridine) Copolymers in a Selective Ionic Liquid Solvent

Abstract: The phase behavior of poly(styrene-block-2-vinylpyridine) copolymer solutions in an imidazolium bis(trifluoromethane)sulfonamide ([Im][TFSI]) ionic liquid has been studied using small-angle X-ray scattering (SAXS) and optical transmission characterization. Through scaling analysis of SAXS data, we demonstrate that the [Im][TFSI] ionic liquid behaves as a selective solvent toward one of the blocks. We observe lyotropic and thermotropic phase transitions that correspond qualitatively to the phase behavior observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 55 publications
7
90
1
Order By: Relevance
“…Figure 9b plots inter‐domain d spacings (Table S2, Supporting Information) as a function of IL content (wt%), which shows that d spacing between polyurethane hard domains linearly increased with IL content. Previous studies have showed that the preferential incorporation of IL into block copolymers leads to increased d spacing due to the conformational change of polymer chains in the presence of IL 32. Segalman and co‐workers32 studied a polystyrene‐ block ‐poly(2‐vinylpyridine) block copolymer incorporated with EMIm TFSI IL, which displayed systematic increase in d spacing with IL content.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 9b plots inter‐domain d spacings (Table S2, Supporting Information) as a function of IL content (wt%), which shows that d spacing between polyurethane hard domains linearly increased with IL content. Previous studies have showed that the preferential incorporation of IL into block copolymers leads to increased d spacing due to the conformational change of polymer chains in the presence of IL 32. Segalman and co‐workers32 studied a polystyrene‐ block ‐poly(2‐vinylpyridine) block copolymer incorporated with EMIm TFSI IL, which displayed systematic increase in d spacing with IL content.…”
Section: Resultsmentioning
confidence: 99%
“…8 Meanwhile, ILs are frequently doped with lithium salts to compensate for their large ion size to further improve the device performance. [10][11][12][13] Among many IL-based polymer electrolytes, IL-loaded electrospun mats have garnered increasing interest because in the mats there are interconnected pores between the randomly laid bers, which facilitate electrolyte uptake and transport of ions. Thus, IL-based gel polymer electrolytes (GPEs), which consist of IL immobilized in a polymer matrix, are an attractive alternative to the IL-based liquid electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45] More recently, there have been reports on more concentrated systems where it has been demonstrated that blending ILs with BCPs such as PS-b-poly(2-vinyl pyridine), [46][47][48] PS-b-poly (ethylene oxide) 49 [PEO], and PEO-b-poly(propylene oxide)-b-PEO 50 can lead to changes in morphology and d-spacing of the phase-separated domains. In this study, we blend 1-ethyl-3-methylimidazolium …”
Section: Introductionmentioning
confidence: 99%